Prevalence, intensity and associated risk factors of soil transmitted helminth infections: A comparison between Negritos (indigenous) in inland jungle and those in resettlement at town peripheries - Muslim, Azdayanti (PLoS Negl Trop Dis, 2019)
BACKGROUND: Formerly known as the Malaysian hunter gatherers, the Negrito Orang Asli (OA) were heavily dependent on the forest for sustenance and early studies indicated high prevalence of intestinal parasitism. Initiation of a redevelopment program in the 1970s aimed to demarginalize the OA was expected to reduce soil transmitted helminth (STH) infections. Gradually, the OA were relocated to new resettlement areas at the peripheries. The aim of this study was to compare STH infections between Negritos who are still living in the inland jungle with those living in resettlements. METHODOLOGY/PRINCIPAL FINDINGS: A total of 416 Negrito participants were grouped into two categories of communities based on location; Inland Jungle Villages (IJV); and Resettlement Plan Scheme (RPS). Iodine wet mount, formalin-ether sedimentation, modified Trichrome and modified Ziehl-Neelsen staining and Kato-Katz methods were performed on stool samples. A questionnaire was used to collect information regarding demographic, socioeconomic, environmental and hygiene behaviors. Prevalence of STH was significantly higher in IJV (91.3%) versus RPS (83.1%) (P = 0.02). However, the percentage of individuals with severe intensity of Trichuris trichiura infections was significantly higher in the RPS (17.2%) compared to IJV (6.5%) (P = 0.01). Severe Ascaris lumbricoides infection was observed at 20.0% amongst RPS Negritos and 15.0% amongst IJV (P = 0.41). Whilst for hookworm infection, both prevalence and individuals with moderate to severe infections were higher in the IJV (26.2%, 41.0%) versus RPS (18.7%, 24.0%) (P values = 0.08, 0.09), accordingly. The prevalence other intestinal parasitic infections (e.g. Entamoeba sp., Blastocystis and flukes) was also higher in IJV versus RPS. Apart from poor hygienic behaviors as significant risk factors in both communities, low socio-economic status was highly associated with STH infections in RPS (P<0.001) but not significantly associated in IJV. CONCLUSIONS: The findings showed that ex situ development plan by RPS has not profoundly contributed to the STH reduction among the OA. Conversely, burden rate of T. trichiura infections increased due to their extreme poverty and poor hygienic behaviors. Here, we are suggesting biannual mass albendazole intervention (triple dose regimens in RPS, but a single dose in IJV) and community empowerment to both communities. For a long-term and better uptake, these strategies must be done together with the community input and participation, respecting their traditional customs and accompanied by recruitment of more OA people in the health-care taskforce.